1998
DOI: 10.1111/j.1477-9552.1998.tb01275.x
|View full text |Cite
|
Sign up to set email alerts
|

Working Women and Expenditures on Food Away‐From‐Home and At‐Home in Spain

Abstract: s p ' n currently is expmmctng rapid cuhurd and economic changes that innuen@ food markts. In this p a p , the selrclion and purchase o/ food aruayfmm home and at home in Spain me mod& in a twp slagr proms using switching rtgression techniques with explicit accounting for the value of w m m i time availaMr for household production. The mptncd resulk show lhat the value of w m m i time, income, and household demographic variables are important drlcnninank of b t h participation in Ilu market fir andapmditum on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 15 publications
2
26
1
1
Order By: Relevance
“…This model underlies most analyses of FAFH expenditure to date (Manrique & Jensen, 1998;Mutlu & Gracia, 2004;Mutlu & Gracia, 2006;Yen, 1993).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model underlies most analyses of FAFH expenditure to date (Manrique & Jensen, 1998;Mutlu & Gracia, 2004;Mutlu & Gracia, 2006;Yen, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…1 Between 1987 and 1999=2000 the proportion of total food expenditure allocated to FAFH increased from 14% to 23% as illustrated in Table 1. Previous studies analyzing the determinants of FAFH in Europe have tended to focus on the entire market with little regard given for the diversity of the disaggregated sectors considered in this study, namely, quick-service (fast food and takeaway) and full-service (hotel and restaurant meals) (Manrique & Jensen, 1998;Mihalopoulos & Demoussis, 2001). 2 Given the diversity of outlets within the food service sector, a disaggregated approach is important in understanding the dynamics of the FAFH industry.…”
mentioning
confidence: 99%
“…Several studies have shown that time valuation, in particular for the female spouse in the household who participates in the labor market, plays an important role in food away from home demand (Byrne, Capps and Saha, 1996;Jensen & Yen, 1996;Kinsey, 1983;Manrique & Jensen, 1998;Prochaska & Schrimper, 1973;Redman 1980;Yen, 1993). However, quantification of the variable varies across studies.…”
mentioning
confidence: 99%
“…Given that the time costs for meals must consider all aspects, including preparation, eating and cleaning time (35) , this association may be related to a greater amount of time afforded to these women through not having paid work commitments. Alternatively, those who do work may be under more time pressure, which may increase the demand for convenience products such as fast food (24,(36)(37)(38) . Further, blue-collar employees may work non-standard working hours (e.g.…”
Section: Discussionmentioning
confidence: 99%